6ln(x+9)-7lnx=

Simple and best practice solution for 6ln(x+9)-7lnx= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6ln(x+9)-7lnx= equation:


Simplifying
6ln(x + 9) + -7lnx = 0

Reorder the terms:
6ln(9 + x) + -7lnx = 0
(9 * 6ln + x * 6ln) + -7lnx = 0
(54ln + 6lnx) + -7lnx = 0

Combine like terms: 6lnx + -7lnx = -1lnx
54ln + -1lnx = 0

Solving
54ln + -1lnx = 0

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Factor out the Greatest Common Factor (GCF), 'ln'.
ln(54 + -1x) = 0

Subproblem 1

Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(54 + -1x)' equal to zero and attempt to solve: Simplifying 54 + -1x = 0 Solving 54 + -1x = 0 Move all terms containing l to the left, all other terms to the right. Add '-54' to each side of the equation. 54 + -54 + -1x = 0 + -54 Combine like terms: 54 + -54 = 0 0 + -1x = 0 + -54 -1x = 0 + -54 Combine like terms: 0 + -54 = -54 -1x = -54 Add 'x' to each side of the equation. -1x + x = -54 + x Combine like terms: -1x + x = 0 0 = -54 + x Simplifying 0 = -54 + x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| p/s=20 | | 4x^2+12x+9=5 | | 9t-7=t+25 | | 5x-2/3 | | 4t-7=t+25 | | log(5x)=-1 | | 5(4y+3)=8 | | y/5.2=3.4=4.3 | | (8-6i)-(-7+i)= | | 3ax^2+2ax+1=0 | | 0=-1.225x^2+1.73x+1 | | 3s+20=4s | | (a-bi)((a+bi)+1)=11+3i | | -x+2x-1=0 | | 650+88m=650m | | 247*11= | | 2x-14=x+40 | | 0=-12x^2+156x | | 6[1-(5x-2)]=8(3-3x) | | 4q-34=2q | | 3x+15=1x+21 | | 40c^2/8c | | z(z+1)=11+3i | | 7+2z=13 | | 4q-34=29 | | -12x^2+12=156x | | 6p+27=9p | | ax^2+12x+9=0 | | −5=f/5 | | z(z-1)(z+3)=11+3i | | 3ax^2+2ax-1=0 | | (4x-6)/5=90 |

Equations solver categories